The relationship among emotional intelligence, social intelligence and learning behaviour - Praditsang, Mali; Hanafi, Zahyah; Walters, Timothy (Canadian Center of Science and Education, 2015)
The objective of this study was to gauge the level of emotional intelligence, social intelligence and learning behaviour among first-year students at a university in southern Thailand.The study examined whether demographic factors, emotional and social intelligence were related to students’ learning behaviour.The subjects were 569 first-year students in their second semester of the academic year.The study found that emotional intelligence and social intelligence were high while learning behaviour was at a medium level. When hierarchical multiple regression was used to examine the relationship among demographic factors, emotional intelligence, social intelligence and learning behaviour, the findings revealed that father’s education was negatively significant with learning behaviour.Emotional intelligence was not significantly related with learning behaviour. However, social intelligence was significantly related with learning behaviour, except for social cognition, self-presentation, influence and concern.